Highly active bimetallic CuFe-N-C electrocatalysts for oxygen reduction reaction in alkaline media - Kang, Yun Sik; Heo, Yoonhye; Jung, Jae Young; Sohn, Yeonsun; Lee, Soo-Hyoung; Jang, Jue-Hyuk; Kim, Pil; Yoo, Sung Jong (한국공업화학회, 2019)
Here, we prepare a bimetallic CuFe-N-C catalyst for the oxygen reduction reaction (ORR) by annealing metal precursor-adsorbed polyaniline under an NH3 gas atmosphere at high temperature. The catalyst exhibits higher ORR activity and durability than Pt/C and other monometallic Cu (Fe)-N-C catalysts in 0.1 M KOH. The remarkable catalytic activity of the CuFe-N-C catalyst is due to the interaction between Cu and Fe, which facilitates ORR and also results in higher contents of total N and active N species. In the same vein, single cell using the CuFe-N-C catalyst exhibits greatly enhanced performance compared to those using other catalysts. (C) 2018 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.